Regulation of skeletal muscle proteolysis - Slee, Adrian (2005)
Proteolysis is a component of protein turnover, controlled by multiple proteolytic systems. Alterations in system components within skeletal muscle has been associated with hypertrophy, remodelling, atrophy, apoptosis and metabolic dysregulation. Key components may have novel regulatory roles, e. g. calpain-3 and cathepsin-L. Experiments described within this thesis investigated the hypothesis that the gene expression of specific proteolytic system components within skeletal muscle may be co-ordinately regulated and altered during nutritional and pharmacological states known to modify protein turnover and induce muscle growth. Gene expression for multiple components of the calpain system was analysed in calf LD (Longissmus dorsi) by Quantitative Real-Time PCR in a plane of nutrition trial. There were three groups: low (LOW), high (HIGH) plane of nutrition and LOW to HIGH (REFED). Half of each group were slaughtered 48 hrs after refeeding, whilst the remainder were slaughtered 13 days later. Total RNA yield/g LD increased (P < 0.05) across all groups between slaughter dates. Calpain-3 expression increased in LOW and REFED and calpastatin in all groups between slaughter dates, with a trend towards significance (P = 0.073, P=0.085, respectively). In the 1St slaughter, calpain-3 expression had a trend to be lower in the LOW group and values for REFED were similar to HIGH value level. cDNA probes for unique and novel proteolytic system components were generated by RT-PCR and used to investigate the effects of acute and chronic Q-adrenergic stimulation, on the gene expression of those specific components in pig LD, by northern blotting. The ß2-adrenergic agonist clenbuterol (5 ppm) decreased glycogen levels (mg/g LD) (P < 0.001), increased cathepsin-L expression (P < 0.001) and increased E2G 1 values numerically within 24 hrs of treatment. Cathepsin-L was unchanged by adrenaline administration. Calpain-3 was unchanged with either clenbuterol or adrenaline treatment. The significance and implications of the data are discussed.